Implementasi Analisis Markov pada R Studio untuk Model Prediksi Perpindahan Pengguna Transportasi Online - Yerymia Alfa Susetyo (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The development of transportation in Indonesia has entered an era of collaboration with information technology. Online-based transportation has proven to facilitate the mobility of people's lives. The emergence of various online transportation providers in Indonesia requires these providers to have data-based programmed business planning. Predicting customer loyalty is one of the factors considered in business planning. This study aims to predict the switching behavior of online transportation users using Markov Analysis. The study uses data taken from 100 respondents in Jakarta. User switching patterns are analyzed based on the first, second, and third months of online transportation providers used by the respondents. Gojek and Grab are used as the online transportation providers examined in this study. The study results in a Steady State or equilibrium condition, showing that Gojek has a 66% user loyalty rate, while Grab has a 34% user loyalty rate.